2012
DOI: 10.1590/s1984-82502012000400014
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable microparticulate drug delivery system of diltiazem HCl

Abstract: The efficacy of a drug in a specific application requires the maintenance of appropriate drug blood level concentration during a prolonged period of time. Controlled release delivery is available for many routes of administration and offers many advantages (as microparticles and nanoparticles) over immediate release delivery. These advantages include reduced dosing frequency, better therapeutic control, fewer side effects, and, consequently, these dosage forms are well accepted by patients. Advances in polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Similar to the released profile from pure MTF, formulation of MTF in the form of MP–MTF exhibited release behavior that did not depend on the absence/presence of glucose. Compared to the release profile from pure MTF, it was observed that the formulation of MTF into MPs could prolong the release of MTF up to 24 h by following previous studies. , This was due to the cross-linking of gelatin in the MP formulation . These findings indicated that the formulation of MTF into MPs was crucial to obtaining prolonged drug release.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Similar to the released profile from pure MTF, formulation of MTF in the form of MP–MTF exhibited release behavior that did not depend on the absence/presence of glucose. Compared to the release profile from pure MTF, it was observed that the formulation of MTF into MPs could prolong the release of MTF up to 24 h by following previous studies. , This was due to the cross-linking of gelatin in the MP formulation . These findings indicated that the formulation of MTF into MPs was crucial to obtaining prolonged drug release.…”
Section: Resultsmentioning
confidence: 67%
“…DMN may be dissolved in 15 min, but the encapsulation system of MTF in the form of MPs can prolong the permeation time of MTF into the systemic tract. In addition, the GR material in the form of PBA linked to the polymer constituent of the MPs provides a permeation effect of MTF which is accelerated as the glucose level in the medium increases …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S5 †). [32][33][34][35][36] Goodness of t (R 2 ) indicated that the in vitro release of 5-FU and PTX tted well into all models except the zero-order dynamics model, suggesting that (5-FU+PTX)@FHPL can release both drugs in a sustained manner through diffusion and erosion processes.…”
Section: In Vitro Drug Releasementioning
confidence: 97%